The Effect of Competency and Remuneration on Healthcare Workers Performance Mediated By Work Discipline at Rumah Sakit Pusat Pertamina - Sugiarto, Heri; Zainal, Veithzal Rivai (International Journal of Social and Management Studies, 2025)
This study aims to examine and analyze the influence of competency and remuneration on the performance of healthcare workers, with work discipline as an intervening variable. A quantitative research method was employed, and data were collected through the distribution of research instruments to 149 healthcare workers at Rumah Sakit Pusat Pertamina. The data were analyzed used the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results indicate that competency has a positive and significant effect on work discipline and the performance of healthcare workers, remuneration does not have a significant effect on either work discipline or performance, work discipline has a positive and significant effect on performance. Competency also has a positive and significant indirect effect on performance through work discipline, whereas remuneration does not affect performance through work discipline. This study develops a holistic model linking competency and remuneration to healthcare workers’ performance, while also exploring the simultaneous role of work discipline as an intervening variable. It is recommended the hospitals optimize the productivity of healthcare workers by improving a transparent and fair remuneration system, enhancing training and educational opportunities, providing recognition and feedback on employee performance, and reinforcing adherence to work discipline.